|
| 1 | +\chapter{Maximum Likelihood Estimate} |
| 2 | + |
| 3 | +Given some distribution with an unknown parameter $\theta$: |
| 4 | +\[X \thicksim Distribution(\dots \theta \dots)\] |
| 5 | +And a sample taken from the distribution $\underline{X}$: |
| 6 | +\[\underline{X} = (X_1, X_2, \dots, X_n)\] |
| 7 | +We want to know the value of $\theta$ for which the likelihood of the sample occurring is highest. |
| 8 | +\begin{definitionbox}{Likelihood Function} |
| 9 | + The likelihood of some observations $x_1, x_2, \dots, X_n$ occurring given some $\theta$ are: |
| 10 | + \[\begin{split} |
| 11 | + L(\theta) &= P(x_1, x_2, \dots, x_n|\theta) \\ |
| 12 | + &= \prod_{i=1}^n f(x_i|\theta) |
| 13 | + \end{split}\] |
| 14 | + This is as $f$ is the \keyword{probability mass function}, and as each observation is independent we can multiply their probabilities. |
| 15 | +\end{definitionbox} |
| 16 | +\begin{definitionbox}{Log Likelihood Function} |
| 17 | + Used more often than likelihood (easier to work with, and converts decimal small values to large negative values - avoids floating point errors) |
| 18 | + \[l(\theta) = \ln L(\theta)\] |
| 19 | +\end{definitionbox} |
| 20 | +To do this, we construct the likelihood (or log likelihood) function from the distribution and sample in term of $\theta$. |
| 21 | +\\ |
| 22 | +\\ Then we can differentiate the function to determine the value of $\theta$ for the maximum. |
| 23 | +\\ |
| 24 | +\\ This value of $\theta$ is the \keyword{Maximum Likelihood Estimate} ($\hat{\theta}$). |
| 25 | + |
| 26 | +\section{Common Maximum Likelihood Estimates} |
| 27 | +Given a sample $\underline{x} = (x_1, x_2, \dots, x_n)$, we can use formulas for the maximum likelihood. |
| 28 | + |
| 29 | +\subsection{Exponential Distribution} |
| 30 | +\[X \thicksim Exp(\theta) \Rightarrow f(x) = \theta e^{-\theta x}\] |
| 31 | +First we determine the \keyword{likelihood} in terms of $\theta$. |
| 32 | +\[\begin{split} |
| 33 | + L(\theta) &= \prod_{i=1}^n f(x_i) \\ |
| 34 | + &= \prod_{i=1}^n \theta e^{-\theta x_i} \\ |
| 35 | + &= \theta^n\prod_{i=1}^n e^{-\theta x_i} \\ |
| 36 | + &= \theta^n e^{-\theta\sum_{i=1}^n x_i} \\ |
| 37 | + \end{split}\] |
| 38 | +Next we can derive the \keyword{log likelihood} |
| 39 | +\[\begin{split} |
| 40 | + l(\theta) &= \ln L(\theta) \\ |
| 41 | + &= \ln \left(\theta^n e^{-\theta \sum_{i=1}^nx_i} \right)\\ |
| 42 | + &= n\ln \theta -\theta\sum_{i=1}^n x_i \\ |
| 43 | + \end{split}\] |
| 44 | +Next we can differentiate and set equal to zero: |
| 45 | +\[\begin{split} |
| 46 | + \cfrac{dl(\theta)}{d\theta} &= n\cfrac{1}{\theta} - \sum_{i=1}^nx_i = 0\\ |
| 47 | + 0 &= \cfrac{n}{\theta} - \sum_{i=1}^nx_i \\ |
| 48 | + \sum_{i=1}^nx_i &= \cfrac{n}{\theta} \\ |
| 49 | + \theta &= \cfrac{n}{\sum_{i=1}^nx_i} \\ |
| 50 | + \end{split}\] |
| 51 | +Hence the maximum likelihood estimator is the reciprocal of the mean of the sample. |
| 52 | +\[\hat{\theta} = \sfrac{1}{\overline{x}}\] |
| 53 | +\subsection{Geometric Distribution} |
| 54 | +\[X \thicksim Geo(\theta) \Rightarrow f(x) =\theta(1-\theta)^{x - 1}\] |
| 55 | +\[\begin{split} |
| 56 | + L(\theta) &= \prod_{i=1}^n f(x_i) \\ |
| 57 | + & \prod_{i=1}^n \theta(1-\theta)^{x_i - 1} \\ |
| 58 | + & \theta^n \prod_{i=1}^n (1-\theta)^{x_i - 1} \\ |
| 59 | + & \theta^n (1 - \theta)^{\sum_{i=1}^n(x_i - 1)} \\ |
| 60 | + & \theta^n (1 - \theta)^{\left(\sum_{i=1}^nx_i\right) - n} \\ |
| 61 | + \end{split}\] |
| 62 | +Now we find the \keyword{log likelihood}. |
| 63 | +\[\begin{split} |
| 64 | + l(\theta) &= \ln L(\theta) \\ |
| 65 | + &= \ln \left( \theta^n (1 - \theta)^{\left(\sum_{i=1}^nx_i\right) - n} \right) \\ |
| 66 | + &= n\ln\theta +\left(\left(\sum_{i=1}^nx_i\right) - n\right)\ln\left(1 - \theta\right) \\ |
| 67 | + \end{split}\] |
| 68 | +Now we differentiate, and set equal to zero to find $\hat{\theta}$. |
| 69 | +\[\begin{split} |
| 70 | + \cfrac{dl(\theta)}{d\theta} &= \cfrac{n}{\theta} + \left(\left(\sum_{i=1}^nx_i\right) - n\right)\cfrac{1}{\theta - 1} = 0 \\ |
| 71 | + 0 &=\cfrac{n(\theta - 1)}{\theta(\theta - 1)} + \left(\left(\sum_{i=1}^nx_i\right) - n\right)\cfrac{\theta}{\theta(\theta - 1)} \\ |
| 72 | + 0 &=n(\theta - 1)+ \left(\left(\sum_{i=1}^nx_i\right) - n\right)\theta \\ |
| 73 | + 0 &=n\theta - n + \left(\left(\sum_{i=1}^nx_i\right) - n\right)\theta \\ |
| 74 | + n &=\left(\sum_{i=1}^nx_i\right)\theta \\ |
| 75 | + \cfrac{n}{\sum_{i=1}^nx_i} &=\theta \\ |
| 76 | + \end{split}\] |
| 77 | +Hence the maximum likelihood estimator is the reciprocal of the mean of the sample. |
| 78 | +\[\hat{\theta} = \sfrac{1}{\overline{x}}\] |
| 79 | +\subsection{Binomial Distribution} |
| 80 | +\[X \thicksim Binomial(m, \theta) \Rightarrow f(x) =\begin{pmatrix} |
| 81 | + m \\ x |
| 82 | + \end{pmatrix}\theta^x(1 - \theta)^{m-x}\] |
| 83 | +\[\begin{split} |
| 84 | + L(\theta) &= \prod_{i=1}^n f(x_i) \\ |
| 85 | + &= \prod_{i=1}^n \begin{pmatrix} |
| 86 | + m \\ x_i |
| 87 | + \end{pmatrix}\theta^{x_i}(1 - \theta)^{m-x_i} \\ |
| 88 | + &= \prod_{i=1}^n \begin{pmatrix} |
| 89 | + m \\ x_i |
| 90 | + \end{pmatrix} \times \prod_{i=1}^n\theta^{x_i} \times \prod_{i=1}^n(1 - \theta)^{m-x_i} \\ |
| 91 | + &= \prod_{i=1}^n \begin{pmatrix} |
| 92 | + m \\ x_i |
| 93 | + \end{pmatrix} \times \theta^{\sum_{i=1}^nx_i} \times (1 - \theta)^{\sum_{i=1}^n m - x_i} \\ |
| 94 | + &= \prod_{i=1}^n \begin{pmatrix} |
| 95 | + m \\ x_i |
| 96 | + \end{pmatrix} \times \theta^{\sum_{i=1}^nx_i} \times (1 - \theta)^{mn - \sum_{i=1}^n x_i} \\ |
| 97 | + \end{split}\] |
| 98 | +Now we find the \keyword{log likelihood}. |
| 99 | +\[\begin{split} |
| 100 | + l(\theta) &= \ln L(\theta) \\ |
| 101 | + &= \ln \left( \prod_{i=1}^n \begin{pmatrix} |
| 102 | + m \\ x_i |
| 103 | + \end{pmatrix} \times \theta^{\sum_{i=1}^nx_i} \times (1 - \theta)^{mn - \sum_{i=1}^n x_i} \right) \\ |
| 104 | + &= \ln \prod_{i=1}^n \begin{pmatrix} |
| 105 | + m \\ x_i |
| 106 | + \end{pmatrix} + \ln \theta^{\sum_{i=1}^nx_i} + \ln (1 - \theta)^{mn - \sum_{i=1}^n x_i} \\ |
| 107 | + &= \ln \prod_{i=1}^n \begin{pmatrix} |
| 108 | + m \\ x_i |
| 109 | + \end{pmatrix} + \sum_{i=1}^nx_i\ln \theta + \left( mn - \sum_{i=1}^n x_i \right)\ln (1 - \theta) \\ |
| 110 | + \end{split}\] |
| 111 | +Now we differentiate, and set equal to zero to find $\hat{\theta}$. |
| 112 | +\[\begin{split} |
| 113 | + \cfrac{dl(\theta)}{d\theta} &= 0 + \sum_{i=1}^nx_i\cfrac{1}{\theta} + \left( mn - \sum_{i=1}^n x_i \right)\cfrac{1}{\theta - 1}= 0 \\ |
| 114 | + 0 & = \sum_{i=1}^nx_i\cfrac{\theta - 1}{\theta(\theta - 1)} + \left( mn - \sum_{i=1}^n x_i \right)\cfrac{\theta}{\theta(\theta - 1)} \\ |
| 115 | + 0 & = \sum_{i=1}^nx_i (\theta - 1) + \left( mn - \sum_{i=1}^n x_i \right)\theta \\ |
| 116 | + 0 & = \theta\sum_{i=1}^nx_i - \sum_{i=1}^nx_i + mn\theta - \theta\sum_{i=1}^n x_i \\ |
| 117 | + 0 & = - \sum_{i=1}^nx_i + mn\theta \\ |
| 118 | + \cfrac{\sum_{i=1}^nx_i}{mn} & =\theta \\ |
| 119 | + \end{split}\] |
| 120 | +Hence the maximum likelihood estimator is the sample mean divided by the number of trials (for binomial): |
| 121 | +\[\hat{\theta} = \cfrac{\overline{x}}{m}\] |
0 commit comments